MICAI 2007: Advances in Artificial Intelligence
DOI: 10.1007/978-3-540-76631-5_94
|View full text |Cite
|
Sign up to set email alerts
|

E-Gen: Automatic Job Offer Processing System for Human Resources

Abstract: Abstract. The exponential growth of the Internet has allowed the development of a market of on-line job search sites. This paper aims at presenting the E-Gen system (Automatic Job Offer Processing system for Human Resources). E-Gen will implement two complex tasks: an analysis and categorisation of job postings, which are unstructured text documents (e-mails of job listings possibly with an attached document), an analysis and a relevance ranking of the candidate answers (cover letter and curriculum vitae). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
0
20
0
1
Order By: Relevance
“…A categorization of text segments (preamble, skills or profile, mission) is obtained by using a SVM classifier (Fan, Chen, & Lin, 2005). This preliminary classification is then transmitted to a ''corrective'' post-process which improves the quality of the solution (Module 1, described in Kessler et al, 2007). Preliminary experiments showed that segment categorization without segment position in job posting is not enough and may be a source of errors.…”
Section: System Overviewmentioning
confidence: 98%
See 1 more Smart Citation
“…A categorization of text segments (preamble, skills or profile, mission) is obtained by using a SVM classifier (Fan, Chen, & Lin, 2005). This preliminary classification is then transmitted to a ''corrective'' post-process which improves the quality of the solution (Module 1, described in Kessler et al, 2007). Preliminary experiments showed that segment categorization without segment position in job posting is not enough and may be a source of errors.…”
Section: System Overviewmentioning
confidence: 98%
“…Our first work (Kessler, Torres-Moreno, & El-Bèze, 2007) presented the first module: the identification of different parts of a job offer and the extraction of relevant information (type of contract, salary, localization, etc.). The second module analyses the content of a candidate's e-mail, using a combination of rules and machine learning methods (Support Vector Machines, SVM) and was presented in Kessler, Torres-Moreno, and El-Bèze (2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Other systems such as E-Gen [13] have automated the recruitment process through categorizing job posts using vectorial and probabilistic models. In this context, Support Vector Machine (SVM) classification algorithms are used in order to annotate segments of job posts with the appropriate topics and features.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, Support Vector Machine (SVM) classification algorithms are used in order to annotate segments of job posts with the appropriate topics and features. The main limitation of these approaches is that are subjective to high error rates since they depend on manually developed training corpora [13].…”
Section: Related Workmentioning
confidence: 99%
“…Our previous works present the first module [7], the identification of different parts of a job offer and the second module [8] which analyses the contents of a candidate e-mail with Support Vector Machine [9] and n-gramms approach. We present in this paper a strategy to resolve the last module.…”
Section: A Module To Analyse the Candidate Answers (Splitting E-mailsmentioning
confidence: 99%